Very late stent trombosis. An unpleasant surprise. - César Enrique Filgueiras Frías; Rubén Bestard Bicet; Sara Laria Menchaca; Leonardo López Ferrero; Jesús M. Pérez del Todo; Luis H. Villanueva Ponte (ECIMED, 2011)
The stent thrombosis is a clinical event whose incidence is not well clarified, since, with a lotof frequency, the angiographic confirmation it is not used as an inclusion criteria in clinicaltrials. Although it is a not very common complication, it's severity is given, fundamentally,because their form of presentation is the sudden death or the myocardial infarction with STsegment elevation in 80% of the patients. The case of 58 years old female patient, is presentedwith a very late thrombosis in a conventional stent, 5 years and 8 months after theinstallation of the device in the right coronary artery.